Key Performance Indicators Analysis for Quay Container Crane Performance Assessment (Case Study at Jakarta International Container Terminal) - Pekih, Mufti Imam; Sembiring, Adelina; Santoso, Sugeng (International Journal of Mechanical Engineering Technologies and Applications, 2021)
PT Jakarta International Container Terminal (JICT) is the largest container port in Indonesia. Currently, JICT capacity is 2.5 million TEUs (Twenty-foot Equivalent Units) per year, it continues to strive to improve international services and is supported by adequate container loading and unloading equipment. The requirement to establish common standards in different types of container port equipment and identify performance indicators to assess the performance of container handling equipment has increased. Although the Quay Container Crane (QCC) operating system may be different at each container terminal, there are similarities in its main movements, namely: Main Hoist, Trolley, Gantry, and Boom. By knowing the clock metric for each movement, it is possible to determine the Key Performance Indicator (KPI) that has been adopted and assess the performance of the Quay Container Crane (QCC). The results of the study identified that the value of MMBF (Mean Move Between Failures) decreased due to the accumulation of long-lasting heavy load operations, while the number of maintenance activities for machine parts and working hours continued to increase. Key Performance Indicator (KPI) as a management tool can guide QCC inspections and the results can provide useful insights for improving the performance of equipment and container loading and unloading operations in the future.